1988
DOI: 10.1037/0735-7044.102.2.260
|View full text |Cite
|
Sign up to set email alerts
|

Temporal factors influence recovery of function after embryonic brain tissue transplants in adult rats with frontal cortex lesions.

Abstract: Adult rats with lesions of the medial frontal cortex received implants of frontal cortex taken from embryos on the 19th day of gestation and placed directly into the zone of injury at 7, 14, 30, or 60 days after initial surgery. Another group was given bilateral frontal lesions, followed 20 days later by a second small lesion to enhance the release of putative neurotrophic factors. They then received transplants 7 days after this second operation. All rats began postoperative training on a spatial alternation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…[6,24,53] These improvements do not appear to be related to the presence of host/donor synaptic activity but rather to the production of soluble factors. [25] Although these benefits are not long-lasting, they provided evidence that manipulation of the neurotrophic environment could impact neural function after brain injury.…”
Section: Role Of Nerve Growth Factormentioning
confidence: 95%
See 1 more Smart Citation
“…[6,24,53] These improvements do not appear to be related to the presence of host/donor synaptic activity but rather to the production of soluble factors. [25] Although these benefits are not long-lasting, they provided evidence that manipulation of the neurotrophic environment could impact neural function after brain injury.…”
Section: Role Of Nerve Growth Factormentioning
confidence: 95%
“…[6,24,53] These improvements do not appear to be related to the presence of host/donor synaptic activity but rather to the production of soluble factors.…”
Section: Role Of Nerve Growth Factormentioning
confidence: 99%
“…This presumption was challenged when Stein and colleagues demonstrated recovery in a T-maze delayed alternation task in rats with prefrontal cortex lesions following transplantation of embryonic cortical tissue into the lesion cavity (Labbe et al 1983;Stein et al 1988). This remarkable observation has been replicated in other laboratories (Kesslak et al 1986a;, and similar effects have since been reported on the recovery of a variety of other tasks following transplantation of embryonic cortical tissues (Haun et al 1985;Stein et al 1985;Bermudez-Rattoni et al 1987;Kolb et al 1988;Escobar et al 1989).…”
Section: Grafts To Deliver Trophic Factorsmentioning
confidence: 99%
“…However, this conclusion turns out to be premature. For functional efficacy, the timing of the lesion, transplantation and testing is critical with no more than a few days separating each stage of the experiments (Kesslak et al 1986 a;Kolb et al 1988;Stein et al 1988), before any connections have had time to develop. Indeed, recovery may subsequently wane once graft-host connections do become established .…”
Section: Grafts To Deliver Trophic Factorsmentioning
confidence: 99%
“…30 On the one hand, this perspective led to the bleak conclusion that efforts to rehabilitate stroke patients were doomed to fail. On the other hand, this view suggested that the behavioral correlates of specific cortical and subcortical regions could be determined in a straightforward manner by comparing the performances of normal subjects with the performances of patients who sustained lesions in particular structures.…”
Section: Potential Role In Clinical Practicementioning
confidence: 99%